2008
DOI: 10.1097/bpo.0b013e318186bdcd
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Supracondylar Humerus Fracture Pinning for Slightly Malreduced Fractures

Abstract: Consider a 3-pin pattern, either 3 laterally divergent pins or 2 lateral pins and 1 medial pin, for SCH fractures when a less than complete anatomical reduction is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 39 publications
2
38
0
7
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14] Although numerous biomechanical 10,13,[15][16][17][18] and clinical studies [3][4][5][6][7][8][9][10][11][12][13][14]19 have documented the benefits and limitations of various pin constructs, none have adequately addressed or isolated pin size and its role in fracture fixation and complication risk. Our goal was to review our experience with Wilkinsmodified Gartland type-III pediatric SCH fractures treated with closed reduction and percutaneous pinning to evaluate the effects of pin size (through the use of a pin size ratio, comparing pin diameter to humeral midshaft cortical thickness) within 2 different pin constructs on the maintenance of reduction and the risk of surgical complications.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Although numerous biomechanical 10,13,[15][16][17][18] and clinical studies [3][4][5][6][7][8][9][10][11][12][13][14]19 have documented the benefits and limitations of various pin constructs, none have adequately addressed or isolated pin size and its role in fracture fixation and complication risk. Our goal was to review our experience with Wilkinsmodified Gartland type-III pediatric SCH fractures treated with closed reduction and percutaneous pinning to evaluate the effects of pin size (through the use of a pin size ratio, comparing pin diameter to humeral midshaft cortical thickness) within 2 different pin constructs on the maintenance of reduction and the risk of surgical complications.…”
mentioning
confidence: 99%
“…As a result of that study, they reported that they achieved more stable fixation with three-wire configurations. Likewise, it was determined in biomechanical studies that stable fixation was obtained from cross K-wire fixation and that performing additional K-wire from the lateral side increased the stability (5,(11)(12)(13)). In the current study, we performed an application of cross K-wire and obtained more stable fixation with additional K-wire from the lateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Although some clinical studies have recommended maximum spread between divergent pins at the fracture to optimize stability [9,14,19] , but the literature is scant regarding the optimum entry point for the lateral pinning for the supracondylar humerus fracture to obtain maximum stability. Some biomechanical studies favor direct lateral epicondyle, extraarticular entry [4,5] , whereas others advocate capitellar or paraolecranon starting point [7,9,12] . So we decided to analyze our cases of supracondylar fracture humerus in children to resolve the basic question of: Does the entry point of the pins placed laterally have an influence on the outcome of the supracondylar humeus fracture?…”
Section: Introductionmentioning
confidence: 99%
“…Other treatment options are plate/screw fixation, external fixation and so on. Although closed manipulation and percutaneous K-wire stabilization is the gold standard for displaced supracondylar fractures of the humerus in children, optimal pin configuration is still not clear [1,[4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation